2017
DOI: 10.1186/s40168-017-0270-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking microbial colonization in fecal microbiota transplantation experiments via genome-resolved metagenomics

Abstract: BackgroundFecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridium difficile infection and shows promise for treating other medical conditions associated with intestinal dysbioses. However, we lack a sufficient understanding of which microbial populations successfully colonize the recipient gut, and the widely used approaches to study the microbial ecology of FMT experiments fail to provide enough resolution to identify populations that are likely responsible for FMT-derived b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 65 publications
7
95
0
Order By: Relevance
“…Studies using genome assembly from metagenomic data to track transplantation of microbes during FMT, which provides more discrete taxonomic resolution than 16S rRNA gene-based surveys, have made similar observations (52, 53). A recent study in two patients with CDI treated with FMT demonstrated that Bacteroidales, but not Clostridiales, were more likely to colonize individuals (52).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies using genome assembly from metagenomic data to track transplantation of microbes during FMT, which provides more discrete taxonomic resolution than 16S rRNA gene-based surveys, have made similar observations (52, 53). A recent study in two patients with CDI treated with FMT demonstrated that Bacteroidales, but not Clostridiales, were more likely to colonize individuals (52).…”
Section: Discussionmentioning
confidence: 87%
“…A recent study in two patients with CDI treated with FMT demonstrated that Bacteroidales, but not Clostridiales, were more likely to colonize individuals (52). Following FMT in obese individuals, Li et al identified that the dominance and resilience of transplanted species such as Roseburia hominis , Ruminococcus lactaris , and Akkermansia muciniphila were not consistently observed across individuals (53).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a single stool sample collected previously from a fecal microbiota transplant donor [52]. Sample collection was approved by University of Chicago Ethics Committee and by the University of Chicago Institutional Review Board (IRB 132-0212) and written and informed consent was obtained for the stool donor.…”
Section: Human Stool Sample Collection and Droplet Cultivationmentioning
confidence: 99%
“…This suppression of Proteobacteria populations may play an important role in resetting intestinal immune homeostasis, as several species of Proteobacteria are capable of thriving in the inflamed intestine and perpetuating continued inflammation (reviewed in (162)) The stability and similarity of recipients’ microbiota following transplant when compared to donor can vary, suggesting that some microbiota compositions may be more stable (160). In a recent study utilizing shotgun metagenomic sequencing to examine microbial colonization following FMT, Lee et al (163) observed a significant increase in Bacteroidetes post-transplant and, interestingly, a negative correlation between genes involved in sporulation and successful colonization of the FMT recipient. This suggests that alternative treatments that rely heavily or solely on spore forming bacteria (such as Seres Therapeutics SER-109, described in detail below) may suffer from limited colonization efficiency.…”
Section: Recolonization Of Gastrointestinal Tract (Git) After Fmtmentioning
confidence: 99%
“…(Although there is some support for diagnosis based solely upon a positive NAAT in the presence of symptoms, other experts recommend use of a multi-step approach to distinguish asymptomatic from symptomatic colonization (reviewed in (45)). The analysis also suggested that the 1 × 10 8 spores received by patients in the Phase II trial (Phase I recipients received doses from 3 × 10 7 to 2 × 10 9 spores) may have been suboptimal – possibly due to the limited colonization efficiency of spore forming bacteria (163). Despite the setback, Seres Health recently announced (June 12, 2017) the initiation of a Phase 3 SER-109 clinical study (ECOSPOR III) in patients with multiply recurrent C. difficile infection.…”
Section: Alternatives To Fmtmentioning
confidence: 99%